Faktor- Faktor yang Berhubungan dengan Kecerdasan Emosional dan Kinerja Penyuluh Pertanian Tanaman Pangan di BP3K Kecamatan Lambuya Kabupaten Konawe - Batoa, Hartina; Sidu, Dasmin; Nurmayasari, Nurmayasari (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2012)
The factors that relate to emotional intelligence and performance of food crop agriculture extension in the agricultural extension central, fisheries and forestry in Lambuya Subdistrict, Konawe Regency”. The research objectives to know the level of intelligence food crop agriculture extension, and to know the factors that relate to emotional intelligence with the performance of food crop agriculture extension in the agricultural extension central, fisheries and forestry (BP3K) Lambuya Subdistrict, Konawe Regency. The achievement of research objectives done by taking two variables namely emotional intelligence variable which includes: (to know self emotional, managing emotions and to motivate themselves, to identify emotions in others, developing relationships with others) and performance of field agriculture extension which includes: (the quality and quantity of work, the knowledge and job skills, creativity, cooperation, and initiative). The sampling is done by using saturated (census) method sampling. The emotional intelligence level and performance of extension can be determined by using the interval equation. Whereas to know the relationship emotional intelligence and performance of Food Crop Agriculture Extension used rank Spearman correlation analysis. The research result shows that there is a factor that relates to emotional intelligence and performance of food crop agriculture extension which includes: developing self-relationships classified always with the percentage (42, 85%), have a significant relationship to performance of food crop agriculture extension whereas to know emotions, managing emotions variable, motivate self and to identify emotion in others, did not have a significant relationship .